2018
DOI: 10.1177/1687814018817194
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and design of the power law damping based on the nonlinear vessel isolation system

Abstract: In this study, the applications of the cubic power law damping in vessel isolation systems are investigated. The isolation performance is assessed using the force transmissibility of the vessel isolation system, which is simplified as a multipledegree-of-freedom system with two parallel freedoms. The force transmissibilities of different working conditions faced in practice are discussed by applying the cubic power law damping on different positions of the vessel isolation system. Numerical results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The appropriate cubic nonlinear damping can keep the resonant frequency unaffected for the floating raft isolation system. 14 The resonant frequencies of the isolation system are ω 1 max = 6 . 13 Hz and ω 2 max = 12 . 77 Hz , respectively.…”
Section: The Ofrf Design Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The appropriate cubic nonlinear damping can keep the resonant frequency unaffected for the floating raft isolation system. 14 The resonant frequencies of the isolation system are ω 1 max = 6 . 13 Hz and ω 2 max = 12 . 77 Hz , respectively.…”
Section: The Ofrf Design Applicationmentioning
confidence: 99%
“…They established the relationship between the system output frequency response and parameters that define the system nonlinearity by employing the output frequency response function (OFRF) approach. Wang et al 14 presented the effects of the cubic nonlinear damping on the vessels’ floating-raft isolation system, and the single diesel engine rotating condition and the double diesel engine rotating condition were considered. Zhu and Lang 15,16 derived an efficient algorithm based on the OFRF concept in order to facilitate the nonlinear systems design in the frequency domain, and provided a general design procedure for a nonlinear auto regressive with exogenous (NARX) inputted model.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the bearing with lower vertical stiffness can effectively isolate long-term ground vibration [23]. Different isolation systems and the material characteristics of isolation bearings can have an impact on the isolation effect [24][25][26][27][28]. Zhang et al mainly studied the seismic performance of rubber isolation bearings and found that natural rubber bearings have good isolation effects [29].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nonlinear isolators have drawn increasing attention since they possess the advantage of mitigation effectiveness compared with the linear ones. [3][4][5] The characteristics of many different kinds of nonlinear isolators in recent years have been summarized by Ibrahim,6 in which a group of isolators that utilize the nonlinear stiffness mechanism to lower their natural frequencies have been confirmed in mitigations of low-frequency vibrations. Zhang et al, 7 Carrella et al, 8,9 and Le and Ahn 10 investigated a novel combined positive and negative stiffness isolator (CPNSI) to mitigate wide-band vibrations.…”
Section: Introductionmentioning
confidence: 99%